Fitness costs of animal medication: antiparasitic plant chemicals reduce fitness of monarch butterfly hosts. (21st July 2016) - Tao, Leiling; Hoang, Kevin M.; Hunter, Mark D.; de Roode, Jacobus C.
Summary: The emerging field of ecological immunology demonstrates that allocation by hosts to immune defence against parasites is constrained by the costs of those defences. However, the costs of non‐immunological defences, which are important alternatives to canonical immune systems, are less well characterized. Estimating such costs is essential for our understanding of the ecology and evolution of alternative host defence strategies. Many animals have evolved medication behaviours, whereby they use antiparasitic compounds from their environment to protect themselves or their kin from parasitism. Documenting the costs of medication behaviours is complicated by natural variation in the medicinal components of diets and their covariance with other dietary components, such as macronutrients. In the current study, we explore the costs of the usage of antiparasitic compounds in monarch butterflies ( Danaus plexippus ), using natural variation in concentrations of antiparasitic compounds among plants. Upon infection by their specialist protozoan parasite Ophryocystis elektroscirrha, monarch butterflies can selectively oviposit on milkweed with high foliar concentrations of cardenolides, secondary chemicals that reduce parasite growth. Here, we show that these antiparasitic cardenolides can also impose significant costs on both uninfected and infected butterflies. Among eight milkweed species that vary substantially in their foliar cardenolide concentration and composition, we observed the opposing effects of cardenolides on monarch fitness traits. While high foliar cardenolide concentrations increased the tolerance of monarch butterflies to infection, they reduced the survival rate of caterpillars to adulthood. Additionally, although non‐polar cardenolide compounds decreased the spore load of infected butterflies, they also reduced the life span of uninfected butterflies, resulting in a hump‐shaped curve between cardenolide non‐polarity and the life span of infected butterflies. Overall, our results suggest that the use of antiparasitic compounds carries substantial costs, which could constrain host investment in medication behaviours. Abstract : The costs of non‐immunological defences against parasites, such as behavioural defences, are not well characterized. Monarch butterflies can use cardenolides from their host plants as medication against their parasites. Here, the authors showed that while cardenolides increased both monarch tolerance and resistance to disease, they also reduced their survival and life spans.